POVERTY AND WOMEN'S ACCESS IN HIGHER EDUCATION: DYNAMICS, PROSPECTS, SHARED CHOICES OF LIMAN-BENAWI WOMEN EDUCATION - Nugroho, Dwi; Anzany, Audy; Fajri, Trio (Jurnal Studi Gender dan Anak, 2023)
Family financial factors and the women social construction are obstacles to women's education. Many of the women who dropped out of school were identified because they were unable to build two-way discussions, so negotiations related to education were never accommodated. This study examines and analyses how women negotiate with parents regarding family culture and economy dynamics, prospects for women, and how to shift them into joint decisions. This qualitative study uses a phenomenological approach by conducting observations, interviews, and documentation studies. The results reveal that some young women from low-income families can continue their education to the tertiary level. Their ability to survive and negotiate with parents and other family members can resolve financial problems and patriarchal culture. Parents who initially did not support them, in turn, encouraged their daughters to continue their education with the consequence of having to work because the family's economy could not cover college costs. These findings indicate that so far gender discrimination in women's education, related to finance and culture, still occurs massively in rural community entities, and this requires cooperative efforts and intense communication to find the best solution. Keywords: Poverty, Women's Education, Gender, Liman Benawi Abstrak Faktor keuangan keluarga dan konstruksi sosial perempuan menjadi penghambat pendidikan perempuan. Banyak perempuan yang putus sekolah teridentifikasi karena tidak mampu membangun diskusi dua arah, sehingga negosiasi terkait pendidikan tidak pernah terakomodasi. Penelitian ini bertujuan untuk melihat dan menganalisis bagaimana perempuan bernegosiasi dengan orang tua mengenai dinamika budaya dan ekonomi keluarga, prospek perempuan, dan bagaimana menggesernya menjadi keputusan bersama. Penelitian kualitatif ini menggunakan pendekatan fenomenologi dengan melakukan observasi, wawancara, dan studi dokumentasi. Hasilnya menunjukkan bahwa sebagian remaja putri dari keluarga miskin dapat melanjutkan pendidikan ke jenjang perguruan tinggi. Kemampuan mereka bertahan untuk bernegosiasi dengan orang tua dan anggota keluarga lainnya membuat masalah keuangan dan budaya patriarki dapat teratasi. Orang tua yang awalnya tidak mendukung, pada gilirannya mendorong anak perempuannya untuk melanjutkan pendidikan dengan konsekuensi harus bekerja karena ekonomi keluarga tidak mampu menutupi biaya kuliah. Temuan ini menunjukkan bahwa selama ini diskriminasi gender dalam pendidikan perempuan, terkait keuangan dan budaya, masih terjadi secara masif di entitas masyarakat pedesaan dan hal ini memerlukan upaya kerjasama dan komunikasi yang intens untuk mencari solusi terbaik. Kata kunci: Kemiskinan, Pendidikan Perempuan, Gender, Liman Benawi